Does interest rate matter to the Ghanaian stock market?. (2016) - Asamoah, Lawrence Adu; Agana, Joseph Akadeagre; Sakyi, Daniel
Stock market and interest rate are two vital factors for financial deepening and economic development of any country. Understanding the effects of interest rate on stock market performance provides important implications for policies towards financial market development. This paper investigates the impact of interest rate on stock market capitalisation in Ghana using monthly data for the period July 2011 to April 2015. The autoregressive distributed lag bounds test approach to cointegration was used for the estimation. The result reveals that, in the long run, interest rate improves stock market capitalisation whilst the opposite is true for the short run. Specifically, the results indicate that, in the long run, long term interest rate has greater impact on stock market capitalisation than short term ones. In the short run, however, long term interest rate has the least impact. The paper concludes that a considerable control of interest rate in Ghana will be of great benefit in the short term for stock market development.